Archiving Primary Data: Solutions for Long-Term Studies. (October 2015) - Mills, James A.; Teplitsky, Céline; Arroyo, Beatriz; Charmantier, Anne; Becker, Peter. H.; Birkhead, Tim R.; Bize, Pierre; Blumstein, Daniel T.; Bonenfant, Christophe; Boutin, Stan; Bushuev, Andrey; Cam, Emmanuelle; et al.
<x xml:space="preserve">Abstract</x> The recent trend for journals to require open access to primary data included in publications has been embraced by many biologists, but has caused apprehension amongst researchers engaged in long-term ecological and evolutionary studies. A worldwide survey of 73 principal investigators (Pls) with long-term studies revealed positive attitudes towards sharing data with the agreement or involvement of the PI, and 93% of PIs have historically shared data. Only 8% were in favor of uncontrolled, open access to primary data while 63% expressed serious concern. We present here their viewpoint on an issue that can have non-trivial scientific consequences. We discuss potential costs of public data archiving and provide possible solutions to meet the needs of journals and researchers.